2022
DOI: 10.3389/fonc.2022.906711
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index and Survival of Patients With Colorectal Cancer: A Meta-Analysis

Abstract: BackgroundGeriatric nutritional risk index (GNRI) is an indicator of nutritional status derived by serum albumin level and ideal body weight, which has been proposed as a predictor of prognosis for elderly population with various clinical conditions. The objective of the meta-analysis was to comprehensively evaluate the association between baseline GNRI and survival of patients with colorectal cancer (CRC).MethodsCohort studies were identified by search of PubMed, Embase, and Web of Science databases from ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…However, patients who reported the lowest values of serum albumin were mainly suffering from gastrointestinal tumors demonstrating a major risk of malnutrition with respect to patients affected by other types of tumors. This aspect was also demonstrated by the GNRI score, which showed the greatest nutritional risk more than all the other instruments used [39,40]. The accuracy of GNRI allowed early detection in patients where other tests did not detect the problem.…”
Section: Discussionmentioning
confidence: 81%
“…However, patients who reported the lowest values of serum albumin were mainly suffering from gastrointestinal tumors demonstrating a major risk of malnutrition with respect to patients affected by other types of tumors. This aspect was also demonstrated by the GNRI score, which showed the greatest nutritional risk more than all the other instruments used [39,40]. The accuracy of GNRI allowed early detection in patients where other tests did not detect the problem.…”
Section: Discussionmentioning
confidence: 81%
“…Nomograms based on these parameters can also be explored in future studies. Many meta-analyses have recently reported the prognostic significance of the GNRI in a variety of solid tumors (31)(32)(33)(34)(35). A recent meta-analysis including 3,981 patients showed the pretreatment GNRI was significantly associated with prognosis in patients with esophageal cancer, and a lower GNRI predicted a worse survival rate (32).…”
Section: Discussionmentioning
confidence: 99%
“…To date, multiple meta-analyses have explored the prognostic role of the GNRI in cancer patients. Zhao et al included nine studies involving 3,658 participants and demonstrated that colorectal cancer patients with a lower baseline GNRI showed worse OS (HR = 2.39, 95% CI: 1.78–3.23, P < 0.001) and progression-free survival (PFS) (HR = 1.77, 95% CI: 1.38–2.26, P < 0.001) ( 14 ). Sun et al showed that a lower GNRI was significantly related to poor OS (HR = 2.01, 95% CI: 1.65–2.44, P < 0.001) and PFS/CSS (HR = 1.81, 95% CI: 1.48–2.22, P < 0.001) ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) patients were pathologically diagnosed with gastric cancer; (2) patients received surgical treatment, and GNRI was calculated as [1.489 × serum albumin level (in g/l)] + [41.7 × present weight/ideal weight (in kg)] before the surgery ( 14 ); (3) the association of preoperative GNRI with postoperative overall survival (OS), cancer-specific survival (CSS) or complications was explored; and (4) hazard ratios (HRs) with 95% confidence intervals (CIs) for OS and CSS were reported in the articles directly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation